A Quest to Cosmological Ideas Revealed in Buddhist Perspective - Muhunthan, S. (Buddhist and Pali University of Sri Lanka., 2023)
The term "Cosmology" denotes learning about the nature of this universe. In Indian schools of thought, the word "Andam" was commonly used to mean the universe. The English word "Cosmology" has been derived from the Greek words "Kosmos" and Logia". Etymologically, the Greek word, "Kosmos" is interpreted as the "World". Logia would mean learning or the field of knowledge. Thus, the word "Cosmology" is defined in etymological dictionaries, as the study of the origin, evolution, and structure of the universe. There are also scholars who interpret cosmology on the grounds not only of philosophy but also of science.Thereby cosmology is viewed in conjunction with astronomy and physics. Hence the role of religious and philosophical traditions gains much prominence in understanding cosmology. While religious and cultural myths occupy a dominant place in the formation of the concept of cosmology. Buddhist thought and practice came to be known as an evolutionary phenomenon in Indian history with the great Awakening {sambodhi) of Gautama the Buddha. It is a fact that Buddhism is one of the oldest religions of the world. Theory of Dependent origination (Pratitya-samutpada), Philosophy of Dynamism, Cosmic Evolution, Spatial Cosmology and Vertical Cosmology are identified are some of the vital concepts in the Buddhist philosophy. These concepts are also found to have some scientific relevance. This research article attempts to explore the significant features of the cosmological concepts revealed in the Buddhist phlosophy. It is also possible to identify the ideas that are precursors to the later cosmological studies. The main objective of this research is to divulge the salient features of the Buddhist Cosmology. This research is basically following the descriptive methodology. In appropriate circumstances the data is subject to content analysis.
Keywords: Cosmology; Theory of Dependent origination; Cosmic evolution; Buddhist philosophy; Philosophy of dynamism